The Effect of Live Streaming on Impulse Buying from an Affordance Perspective on Tiktok Platform - Aldi Maulana Putra; Ilsya Hayadi (UNIVED Press, 2024)
This research aims to examine the effect of live streaming (visibility, trading, and meta voicing) on impulse buying through immersion from an affordance perspective on the TikTok platform. The data used in this research is primary data. This research is included quantitative research with a purposive sampling technique. The population of this research consists of all individuals who have made purchases through live streaming on TikTok, with a total of 200 respondents. This research uses SEM-PLS version 4.0. The results of this research show that trading and meta voicing significant effect on immersion and impulse buying. Then immersion is able to mediate the trading and meta voicing with impulse buying. Meanwhile, visibility has no significant effect on immersion and impulse buying, and immersion is also unable to mediate the relationship between visibility and impulse buying.